To solve the system by substitution, we can set the two equations equal to each other:
-3x + 4 = x
Next, we can combine like terms:
-3x - x = -4
Simplifying, we have:
-4x = -4
Dividing both sides by -4:
x = 1
Now that we found the value of x, we can substitute it into either equation to find the value of y. Let's use the first equation:
y = -3(1) + 4
y = -3 + 4
y = 1
Therefore, the solution to the system of equations is x = 1 and y = 1.
Solve the system by substitution.
y, equals, minus, 3, x, plus, 4
y=
−3x+4
y, equals, x
y=
x
1 answer